Application of a Cold Patch for Relieving Pain after Transepithelial Photorefractive Keratectomy - Yuan Zeng; Yi Li; Jian-Hua Gao (Pain Research and Management)
Although photorefractive keratectomy often results in better corneal stability and fewer corneal flap complications than LASIK, pain remains a major drawback of the procedure. The authors compared the safety and efficacy of a postoperative cold patch versus intraoperative application of a chilled balanced salt solution on transepithelial photorefractive keratectomy-related postoperative pain.